Recurrence pattern and its risk factors in patients with resected pancreatic ductal adenocarcinoma – A retrospective analysis of 272 patients - Brunner, Maximilian; Flessa, Maarten; Jacobsen, Anne; Merkel, Susanne; Krautz, Christian; Weber, Georg; Grützmann, Robert (Pancreatology, 2024)
Background: The aim of this study was to investigate the patterns of recurrence and their associated risk factors in patients who underwent resection for pancreatic carcinoma. Methods: This retrospective study included 272 patients, who underwent Ro/R1-resection of PDAC from 2005 to 2020 at the University Hospital Erlangen. Risk factors for different recurrence patterns and the prognostic value of recurrence pattern on the overall survival after recurrence were evaluated. Results: 61 % of the patients experienced recurrence, mostly within the first 12 postoperative months (62 %) and in the form of metastases (87 %). The median overall survival from recurrence was 9.2 months. The preoperative absence of diabetes and the presence of lymph node metastasis were independent risk factors for recurrence and a preoperative CA19-9 exceeding 97 U/ml for early recurrence. Additionally, lymph node metastases were associated with a higher risk of metastatic recurrence. Early recurrence, but not the site of recurrence, was identified as an independent prognostic factor for worse overall survival from recurrence. Conclusion: The occurrence of recurrence and especially of early and metastatic recurrence are associated with a worse overall survival. Patients lacking preoperative diabetes, having high preoperative CA19-9 values and lymph node metastases are particularly at risk for (early) recurrence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Early recurrence; Locoregional recurrence; Overall survival; Pancreatic ductal adenocarcinoma; Recurrence; Resection; Surgery